Analysis of the Flexing Phenomenon in Social Media from a Hadith Perspective with a Psychological Approach - Aeni, Dinie; Busro, Busro; Fikra, Hidayatul (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2023)
Flexing, or showing off wealth, has become a new phenomenon that has caused a stir on social media. This study aims to discuss flexing from the perspective of hadith. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is a psychological approach by analyzing the hadith matan. The material object of this research is the phenomenon of flexing behaviour on social media. The results of this study indicate that flexing behaviour is strictly forbidden based on the hadith narrated by Abu Dawud No. 3511. The discussion of this study explains that flexing is done when a person has insecurity about himself. Flexing practitioners tend to have emotional intelligence: awareness, empathy, self-regulations, and low social skills. Real rich people never flaunt their wealth, so people flexing their wealth mean they are not really rich. The wealth of the heart is not from material things but is in a heart full of empathy.